Hygrothermal properties of an early 20th century clay brick from eastern France: Experimental characterization and numerical modelling. (1st March 2021) - Aït Oumeziane, Yacine; Pierre, Alexandre; El Mankibi, Fatima; Lepiller, Valérie; Gasnier, Marina; Désévaux, Philippe
Highlights: The hygrothermal properties of an early 20th century clay brick are experimentally characterized. The measured properties show the interesting hygrothermal performance of the material. The temperature-dependent sorption mechanisms are characterized and modelled. Abstract: This paper deals with the experimental hygrothermal characterization of an early 20th century clay brick, representative of historical industrial buildings in eastern France. The renovation and adaptive reuse of industrial heritage buildings require accurate knowledge of the properties of these existing buildings envelopes, for which few data are available in literature. Hence, for example, the application of the French Thermal Regulation to existing old buildings can lead to unexpected damages, like brick spalling due to freeze–thaw phenomenon if a poorly suited additional interior insulation layer is installed. Despite its hygrothermal advantages, external insulation must be avoided for aesthetic and historical values of heritage buildings and it is often prohibited by city codes or historic building preservation regulations. In this context and as literature is scarce, it is relevant to deepen the knowledge of this ancient material in order to better understand the hygrothermal behaviour of old industrial buildings to better preserve them. As a first step towards this goal, the main objective of this paper is to give new data about the hygrothermal properties of an early 20th century brick from eastern France. A comparison between models and measured experimental data is also proposed. In particular, the temperature-dependent hysteretic sorption phenomenon, which occurs in brick, is experimentally and numerically investigated.